Development of low-cost textile sound absorber boards from garment and textile waste using a sponge-like structure - Magdi El Messiry; Elshiamaa M. Eid; Yasmin Ayman (Journal of Engineered Fibers and Fabrics)
The clothing and textile industry generates vast amounts of waste annually, some of which is combusted through incineration or being dumped in landfills, resulting in extensive environmental pollution. This work provides a green approach through recycling clothing and textile waste to manufacture sound-absorbing panels with a new sponge structure. Panels were formed through a blend of textile waste of different fiber diameter, tufting orientation, and porosity. Acoustic properties of the samples were characterized by sound absorption coefficient and sound transmission loss in the frequency range of 500–2000 Hz. The effects of fiber content, layer structure, and bonding process on noise reduction coefficient (NRC) and sound transmission class (STC) were studied. Outcome shows hybrid samples with multilayer sponge-like structures exhibited better acoustic performance with a maximum of 0.65 NRC values and more than 20 dB improvement in sound pressure in mid-frequencies. Hybrid samples of fiber diameters and layered layers showed maximum sound absorption with greater internal porosity and energy dissipation. Sample ID 27 possesses an NRC of 0.9175 and STC of 22.47, greater than double the values described for natural-fiber panels in the literature. In addition to greater absorption coefficients, improved sound insulation (STC > 20) is also provided. All these results clearly show the improved performance of our sponge-like hybrid material from garment textile waste. The study justifies the application of recycled textile materials in green acoustic panel design and the application of the circular economy in the textile sector.